Vietnam Development Report 2019 : Connecting Vietnam for Growth and Shared Prosperity - World Bank Group (Hanoi: Hong Duc Publishing, 2020)
Globally, Vietnam is among the most open economies with a trade-to-GDP ratio of 190 percent in 2018. Through the removal of both tariff and non-tariff barriers and fulfilling its commitment in several regional trade agreements, the country has made remarkable achievements in trade liberalization. Vietnam’s major trade partners located in East Asia, North America, and Europe are reached mostly by sea or air. Trade with bordering neighbors is limited and thus trade across border-crossing points is minimal except for northern borders with China, which has seen growth in recent years. The country’s trade flows are concentrated at twelve of its 48 border gates—two airports, five seaports and five border crossing points—which collectively handled 86 percent of total trade value in 2016.1 As the trade grows, congestion at and near these international gateways and border-crossing points has also increased. In addition to the current major trade partners, various regional trade relations and connectivity initiatives are relevant to Vietnam, including with Southeast Asian neighbors, and South Asia—particularly India—over land, given the rapidly growing trade relationships. In the meantime, Vietnam’s transport network has undergone a significant expansion over the past decades. The most remarkable development in network expansion has occurred in the road sector. As of 2016 the total length of the road network, excluding village roads, reached over 300,000 km, including about 1,000 km of expressways—a fully access-controlled toll road system. Vietnam is endowed with an extensive network of natural waterways, including nearly 16,000 km of managed navigable routes carrying significant traffic around the Red River Delta and Mekong Delta areas. However, only about 2,600 km of the waterways can reliably handle barges greater than 300 deadweight tons, with rudimentary terminal infrastructure at most of its numerous river ports. Vietnam's century-old railway system is mostly single-tracked and non-electrified, which has remained unchanged over the past decades with very limited capital investments